First Cluster of Acute Flaccid Myelitis Related to Enterovirus D-68 in Argentinean Children. (4th October 2017) - Carballo, Carolina; Erro, Marcela Garcia; Sordelli, Nora; Vazquez, Gabriel; Cisterna, Daniel; Mistchenko, Alicia; Cejas, Claudia; Rodriguez, Manlio; Freire, Cecilia; Contrini, María M; Lopez, Eduardo L
Abstract: Background: Acute flaccid Myelitis(AFM) related to enterovirus D68(EVD68) has been reported as sporadic cases worldwide since the outbreak of respiratory illness in USA in 2014. Objective: To describe the first cluster of AFM by EVD68 in Argentina. Methods: prospective-observational study in children admitted to Hospital de Niños "Ricardo Gutiérrez" by Acute Flaccid Paralysis(AFP) from April-August 2016. AFM was defined as AFP with MRI lesions affecting the gray matter of the spinal cord as defined by CDC. RT-PCR was used to identify EVD68 in NPS, CSF, stool samples Results: Nineteen children were admitted by AFP. Six confirmed as AFM: age 40(±22.6) months; 66% female, 50% had history of recurrent wheezing. Prodrome: 100% Upper Respiratory Tract Infection(URTI); 4/6(66%) fever; 1/6(16%) vomiting and abdominal pain. Neurological symptoms appeared 5.2(±6) days after prodrome. All children had acute progressive asymmetric limbs weakness, areflexia, intact sensitivity and severe muscles pain; 5/6(83%) had neck muscles weakness; 3/6(50%) had severe respiratory failure: 2 mechanical ventilation and 1 noninvasive ventilatory assistance; 3/6(50%) needed feeding support; 2/6(33.3%) had cranial nerve dysfunction. None had cognitive disability. CFS findings: 5/6 mononuclear pleocytosis; 2/6 increase of proteins and 1/6 albuminocytological dissociation. Spinal cord lesions in MRI was observed in all patients. EMG showed early signs of denervation and low motor neuron in 5/5 patient. Virology: enterovirus could be identified by RT-nested – PCR and genomic sequencing from nasopharyngeal-swab in 5/6(83%); 4/5 typified as EVD68, in 1/5 viral charge was low for typing. Stool samples: EVD68 was identified in 2/6(33%). CSF samples were negative. Treatment: IV immunoglobulin 5/6(83%) patient; 2/6(33%) systemic corticosteroids; 3/6(50%) required ICU admission. All patients had neurologic motor sequelae; 2/6 remain with chronical ventilatory assistance after 6 months of follow-up. None patient dye. Conclusion: this is the first cluster reported from South America and support evidence for the association of EVD68 and AFM in children. Disclosures: All authors: No reported disclosures.